Application of risk assessment and multi-criteria analysis in contaminated land management in Finland - Sorvari, Jaana (Finnish Environment Institute, 2013)
Land contamination is a significant environmental problem requiring systematic management actions. Defining the type and scale of the actions requires information on the risks involved. The numerous methods available for conducting risk assessment (RA) vary in terms of complexity, level of detail, conservatism, and outcomes. Thus, selecting suitable methods requires information on their applicability in Finnish conditions and at the specific site. On the other hand, it is generally accepted that current contaminated land management (CLM) should not only focus on minimizing site-specific risks, but should also consider overall environmental effects and socio-cultural and socio-economic aspects. Multi-Criteria Analysis (MCA) could then be used as a tool for integrating multidimensional data and generating aggregated information on the consequences of different risk management (RM) options, such as environmental, social, and economic impacts. Nonetheless, such approaches have very seldom been applied in CLM in Finland, probably partly due to a lack of tools specifically developed or modified for Finnish conditions.This research studied the application and suitability of different RA methods for assessing risks and identifying RM needs at some typical contaminated sites in Finland and demonstrated the use of MCA, the emphasis being on soil contamination. The studied RA approaches comprised qualitative rating and quantitative methods that were based on using environmental benchmarks, uptake and exposure models, and multimedia software. To derive estimates of ecological risks, the so-called TRIAD procedure that uses chemical studies, bioassays, and ecological studies was also applied and combined with MCA in order to account for the performance of the study methods, i.e. their ability to depict ecological risks at a study site. Qualitative rating and the statistical Monte Carlo technique provided additional means for uncertainty analysis. A separate study applying the Metaplan technique, interviews, a questionnaire, ...